Pengaruh Media Mimind dalam Model Discovery Learning terhadap Keterampilan Proses Sains Peserta Didik Kelas XI pada Materi Pokok Sistem Koloid - Amalia, Dita Rizky (Chemistry Education Review (CER), 2024)
The research to find out the effect of the miMind media in the Discovery Learning model toward the student’s science process skill on the subject matter of Colloid Systems. The miMind media in the Discovery Learning model as independent variable and the student’s science process skill as the dependent variable. The population in this research is all the students of grade XI MIA MA Pesri Kendari that consist of four classes. Grade XI MIA 2 as experiment group that consist of 21 students and Grade XI MIA 1 as control group that consist of 21 students. The data of research was obtained by observation questionnaire of science process skill and learning implementation observation sheet. The Data were analysed by using descriptive statistics and the inferential statistics. The results of the science process skill hypothesis testing using Independent Sample t-test the values obtained Sig. (2- tailed) as 0,039 < 0,05. It shows that there is the effect of the miMind media in the discovery learning model toward the student’s science process skill of grade XI MIA MA Pesri Kendari on the subject matter of Colloid Systems.